Morphological description of Cyrtopleura costata (Bivalvia: Pholadidae) from southern Brazil - Stakowian, Nicole; Simone, Luiz Ricardo Lopes de (Papéis Avulsos de Zoologia, 2021)
The aim of the study is to describe in detail, for the first time, the internal and external anatomy of Cyrtopleura costata, which displays ellipsoid and elongated valves with beige periostracum, the anterior adductor muscle unites the valves in the pre-umbonal region, with abduction capacity in its dorsal half, sparing the ligament. Two accessory valves are identified: the mesoplax (calcified) located in the umbonal region; and the protoplax (corneus) above the anterior adductor muscle. Internally there is a pair of well-developed apophysis that supports the labial palps and the pedal muscles, and support part of the gills. The posterior half of mantle ventral edge is fused and richly muscular, working as auxiliary adductor muscle. The siphons are completely united with each other, the incurrent being larger than the excurrent. The foot is small (about ⅛ the size of the animal). The kidneys extend laterally on the dorsal surface, solid, presenting a brown/reddish color. The style sac is well developed and entirely detached from the adjacent intestine. The intestine has numerous loops and curves within the visceral mass. The fecal pellets are coin-shaped. The present study certainly may be used as comparative scenario for specimens from other regions of the species range.